The Impact of Economic Shocks on the Tourism Sector in Egypt: Study of the Implications of the Emerging Coronavirus - Mahmoud, Ali (The Arab Journal of Administration, 2022)
The study aimed to shed light on the impact of the implications of the spread of Corona virus on the tourism sector in Egypt, which is one of external economic shocks on the Egyptian economy through dollar tourism revenue, and targeted study testing a basic premise that there is a direct impact and indirect implications of the spread of Corona virus on the sector Tourism in Egypt, and then move the impact to the gross domestic product (GDP). The study found that the prevalence of Corona virus push to slow the visible international trade and invisible movement, and the impact of an adult in the tourism sector, pushing down the cash reserves of foreign hand, and slowing growth rates in output The local community on the other hand, during the period from 2010 to 2020, and the choice came in 2010; To compare the effects of corona’s effects on a year characterized by relative stability, and the choice in 2020, and The slowdown of GDP has led to an increase in unemployment in Egypt. Whereas, the unemployment rate rose to 9.2% in the period from the end of March until the end of April; Due to the Coronavirus pandemic, compared to 7.7% in the first quarter of 2020, and a decrease of 8.1%. as a result of the change due to the spread of the coronavirus.